Effect of autophagy induction and cathepsin B inhibition on developmental competence of poor quality bovine oocytes - Jianye LI; Ahmed Zaky BALBOULA; Mansour ABOELENAIN; Takashi FUJII; Satoru MORIYASU; Hanako BAI; Manabu KAWAHARA; Masashi TAKAHASHI (The Society for Reproduction and Development, 2019)
The present study investigated the effect of autophagy induction and cathepsin B (CTSB) inhibition on developmental competence of poor quality oocytes. Bovine cumulus oocyte complexes (COCs) were classified as good or poor according to their morphology. Autophagy activity was detected in good and poor germinal vesicle (GV) oocytes. Then E-64, a CTSB inhibitor, rapamycin (Rapa), an autophagy inducer, and combined administration was achieved during invitro maturation (IVM) of poor quality COCs followed by detection of autophagy activity. In the next experiment, E-64, Rapa, and E64 + Rapa, were added during IVM to good and poor quality COCs followed by invitro fertilization and culture for 8 days to investigate whether inhibition of CTSB and/or induction of autophagy improve embryonic development and quality. Autophagy activity was significantly lower in poor quality GV oocytes than in good quality ones. E-64, Rapa and E-64 + Rapa treatment during IVM significantly increased autophagy activity in poor quality oocytes. Addition of Rapa in good quality COCs did not increase the blastocyst rate, whereas E-64 increased the blastocyst rate and total cell number (TCN) with decreasing TUNEL-positive cells. In contrast, Rapa treatment in poor quality COCs significantly increased the blastocyst rate and TCN with decreasing TUNEL-positive cells. These results indicate oocyte quality has different responses to intracellular autophagy induction and CTSB activity control by potential autophagy and catabolic status, however, synergetic effect of autophagy induction and CTSB inhibition can increase developmental competence of both good and poor quality COCs, especially rescue effect in poor quality COCs.